330 Tolerability of bevacizumab in elderly ovarian cancer patients (Turbo Study): a case-control study of a real-life experience. (18th September 2019) - Amadio, G; Marchetti, C; Villani, ER; Fusco, D; Stollagli, F; Bottoni, C; Distefano, M; Colloca, G; Fagotti, A; Scambia, G
Abstract : Objectives: Bevacizumab maintenance following platinum-based chemotherapy is an effective treatment for epithelial ovarian cancer (EOC), both in primary and recurrent disease. Our aim was to identify criteria to select elderly patients who can safely benefit from bevacizumab addition. Methods: This is a case-control study on patients with primary or recurrent EOC who received platinum-based chemotherapy plus bevacizumab, between January 2015 - December 2016. Patient characteristics, treatment details and adverse events were reviewed and analyzed in two setting: younger (<65 years, group 1) and elderly (>65 years, group 2). A binary logistic model was applied to correlate clinical variables and severe (grade ≥3) toxicity risk. Results: Overall, 283 patients with EOC were included, with 72 (25.4%) older patients compared with 211 (74.6%) younger women. Bevacizumab had been administered to 234 patients (82.7%) as first-line treatment and in 49 (17.3%) with recurrent disease. At diagnosis, elderly patients presented with at least one comorbidity and were taking at least 1 medication in 84.7% and 80.6% of the cases respectively, compared with correspondingly 47.4% and 37.4% in group 1 (p<0.001). Nonetheless, the occurrence of serous (G3/G4) adverse events did not increase among the older group. Creatinine serum levels > 1.1 g/dl, estimated glomerular filtration rate (eGFR) < 60 ml/min, ≥ 3 comorbidities were independently associated with a higher severe toxicity. Conclusions: Elderly patients with EOC can safely be treated with bevacizumab; factors other than age, as higher creatinine serum levels, eGFR and number of comorbidities should be considered to better estimate bevacizumab-related toxicity risk.